2001
DOI: 10.1002/1097-0142(20010901)92:5<1108::aid-cncr1427>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant chemotherapy for large cell carcinoma with neuroendocrine features

Abstract: BACKGROUND In 1999, the World Health Organization categorized large cell neuroendocrine carcinoma, large cell carcinoma with neuroendocrine differentiation, and large cell carcinoma with neuroendocrine morphology as a variant of large cell carcinoma. Patients with large cell carcinoma with neuroendocrine features have poor prognoses, comparable to those for small cell lung carcinoma. Small cell lung carcinoma is sensitive to chemotherapy; however, it is still unclear whether large cell carcinoma with neuroendo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
61
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 21 publications
0
61
0
4
Order By: Relevance
“…31,32 We observed a 24% 5-year overall survival rate and a 31-month median survival in patients with poorly differentiated LCNEC patients, in line with previous studies that demonstrated a 5-year survival rate between 13% and 57%. 3,8,9,11,22,27,28 In the current study, a high mitotic count and a low number of neuroendocrine markers at immunohistochemistry emerged as prognostic factors for survival in patients with poorly differentiated LCNEC. For the first time, we have identified relevant prognostic impact for the mitotic count in poorly differentiated LCNEC: Patients with < 37 mitoses per 10 HPFs had tumors that were characterized by a less aggressive behavior.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…31,32 We observed a 24% 5-year overall survival rate and a 31-month median survival in patients with poorly differentiated LCNEC patients, in line with previous studies that demonstrated a 5-year survival rate between 13% and 57%. 3,8,9,11,22,27,28 In the current study, a high mitotic count and a low number of neuroendocrine markers at immunohistochemistry emerged as prognostic factors for survival in patients with poorly differentiated LCNEC. For the first time, we have identified relevant prognostic impact for the mitotic count in poorly differentiated LCNEC: Patients with < 37 mitoses per 10 HPFs had tumors that were characterized by a less aggressive behavior.…”
Section: Discussionmentioning
confidence: 58%
“…10,11,13,[22][23][24] Historic LCNEC series have suggested a natural aggressive course with a median survival < 1 year. 25,26 From a prognostic standpoint, LCNEC stage has been described as a major determinant for survival in most studies [27][28][29] but not in all studies. 21 More recently, the degree of endocrine differentiation, p16 expression, and c-kit expression were proposed as new prognostic parameters for survival.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that patients with stage I large cell neuroendocrine carcinoma, who were treated with either neoadjuvant or postoperative adjuvant chemotherapy, had significantly higher survival rates than patients treated only with surgery. 9 The aim of this study was to elucidate the morphological, phenotypical, and genetic characteristics of large cell neuroendocrine carcinoma and compare them with those of small cell carcinoma, to determine the biological differences of these two tumors, and to evaluate the utility of these markers for the diagnosis of neureondocrine tumors and the prognosis according to the expression of these proteins.…”
mentioning
confidence: 99%
“…También hay experiencias con el uso de quimioterapia neoadyuvante, adyuvante y radioterapia 43,45,46 . En la serie de Iyoda, la quimioterapia adyuvante basada en cisplatino, prolongó la supervivencia de los CNCG en estadios iniciales 47 . En nuestra serie (Tabla IV), los dos pacientes tratados con quimioterapia adyuvante tuvieron supervivencias prolongadas.…”
Section: Discussionunclassified